Ultra-Thin GaAs Single-Junction Solar Cells for Self-Powered Skin-Compatible Electrocardiogram Sensors - Nam, Yonghyun; Shin, Dongjoon; Choi, Jun Gyu; Lee, Inho; Moon, Sunghyun; Yun, Yeojun; Lee, Won June; Park, Ikmo; Park, Sungjun; Lee, Jaejin (Small Methods, 2024)
GaAs thin-film solar cells have high efficiency, reliability, and operational stability, making them a promising solution for self-powered skin-conformal biosensors. However, inherent device thickness limits suitability for such applications, making them uncomfortable and unreliable in flexural environments. Therefore, reducing the flexural rigidity becomes crucial for integration with skin-compatible electronic devices. Herein, this study demonstrated a novel one-step surface modification bonding methodology, allowing a streamlined transfer process of ultra-thin (2.3 µm thick) GaAs solar cells on flexible polymer substrates. This reproducible technique enables strong bonding between dissimilar materials (GaAs-polydimethylsiloxane, PDMS) without high external pressures and temperatures. The fabricated solar cell showed exceptional performance with an open-circuit voltage of 1.018 V, short-circuit current density of 20.641 mA cm−2, fill factor of 79.83%, and power conversion efficiency of 16.77%. To prove the concept, the solar cell is integrated with a skin-compatible organic electrochemical transistor (OECT). Competitive electrical outputs of GaAs solar cells enabled high current levels of OECT under subtle light intensities lower than 50 mW cm−2, which demonstrates a self-powered electrocardiogram sensor with low noise (signal-to-noise ratio of 32.68 dB). Overall, this study presents a promising solution for the development of free-form and comfortable device structures that can continuously power wearable devices and biosensors.
Keywords: GaAs solar cells; Organic electrochemical transistors; Powered devices; Self-powered; Self-powered device; Single junction solar cells; Skin-compatible wearable device; Surface-modification; Ultra-thin; Wearable devices; GaAs solar cell; organic electrochemical transistors; self-powered devices; skin-compatible wearable device; surface modification